Lições de um navio baleeiro: uma reflexão sobre o homem, o mar e o animal em Moby Dick, de Herman Melville. - Marília Nogueira Carvalho (2019)
Traditionally, the image of the sea has been associated to horror and fear, propelling the human imagination to create maritime narratives, while reason developed machines and technologies so that sailing would depend more rarely on favourable climate. However, such imagination and developments were not followed by an accurate reflection that takes into account its effects on social relations and human interactions with nature, nowadays in crisis. In this sense, this thesis focuses on Moby Dick (1851), by Herman Melville, in order to investigate the way the relationship between the crew and the sea reflects and questions in which manner humans deal with the natural world and interact with other species. Thus, it is important to highlight the way the narrative represents the imperious advance of humankind over other species and nature itself, reinforcing the contact with the natural and the savage. To do so, the transformation of Ishmael is going to be examined, especially as he interacts with the savage Queequeg and the bond between Ahab and Moby Dick, the whale, which surpasses the level of dominance and utility. Furthermore, we still analyse the bond between humans at the ship, especially the relationship between Ishmael and Queequeg, Ahab and Pip, highlighting the shift of Ishmael’s mood throughout the novel and considering the capacity of humans to act collaboratively.